Design and fabrication of quasi-double-sided silicon drift detector for x-ray detection. (1st March 2023) - Wang, Longjie; Luo, Wei; Jia, Rui; Tao, Ke; Zhang, Danni; Wang, Bolong; Li, Xing
Abstract: Silicon drift detectors (SDDs) with excellent energy resolution are widely used in the field of x-ray detection. Normally, the higher energy resolution of a SDD is mainly due to the lower capacitance compared with other silicon radiation detectors. It is worth noting that the energy resolution is also related to imperfect charge collection and ballistic deficit, which are susceptible to the device drift voltage. However, the maximum drift voltage is limited to twice the depletion voltage because of the reach-through effect in a classical SDD. In order to address this issue, a novel quasi-double-sided silicon drift detector (QD-SDD) was designed and fabricated by the thin film deposition technology. The so-called QD-SDD consists of a symmetrical drift ring structure on both the front and bottom sides. According to the simulation results, QD-SDD can be biased at a larger drift voltage, and thus building a larger drift electrical field than the classical single-sided SDD. Furthermore, the fabricated QD-SDD sensors were characterized using a 55-Fe radioactive source. The energy resolution at the 5.9 keV Mn Kα line can be improved from 210 eV to 170 eV by increasing the bias voltage on the outermost drift ring on both sides from −80 V to −130 V.